Effect of Slow Deep Breathing on Lung Function Among Individuals with Multi-Drug-Resistant Tuberculosis (MDR-TB) at a Regional General Hospital in Indonesia - Hafizah, Nur; Widiharti, Widiharti; Fitrianur, Widya Lita; Ernawati, Ernawati (Fundamental and Management Nursing Journal, 2025)
Introduction: Multi Drug Resistant Tuberculosis (MDR-TB) sufferers experience decreased lung function. Non-pharmacological therapy such as slow deep breathing has been widely applied to improve lung function of individuals with Tuberculosis. However, the results were inconsistant. The aim of this research is to analyze the effect of slow deep breathing on lung function pf individuals with multi-drug resistant (MDR-TB) at the MDR-TB Polyclinic Ibnu Sina General Hospital Gresik, Indonesia. Method: This study employed a quasi-experimental design with a pre-test and post-test. The population consisted of 294. A total of 35 participants were selected using purposive sampling based on inclusion and exclusion criteria. Data collection involved a Standard Operating Procedure (SOP)-guided intervention in slow deep breathing exercises as the independent variable. Lung function, the dependent variable, was measured using a calibrated spirometry device before and after the intervention. An accidental sampling method was applied, focusing on the availability and willing to participate. Results: The results showed of 19 (54.3%) and almost half of participants had abnormal lung function, 16 (45.7%) people. After being given intervention, the majority of particupants presented normal lung function, 21 (65.7%) of them and almost half of them had abnormal lung function, 12 (34.3%) of them. Mc Nemar test to determine the effect of slow deep breathing on lung function was p-value of 0.125 > 0.05. Conclusion: This study documented that slow deep breathing exercises had no significant effect on lung function in individuals with MDR-TB. This likely attributable to other contributing factors, such as routine pharmacological treatment, consistent physical activity, and improved adherence to therapy. These confounding variables may have played a more substantial role in the observed changes. Further research with rigorous experimental designs, involved larger sample sizes, and longer duration of intervention is needed.